Phonaesthetics and personality—Why we do not only prefer Romance languages - Winkler, Anna; Kogan, Vita V.; Reiterer, Susanne Maria (Frontiers in Language Sciences, 2023)
Previous aesthetic research has set its main focus on visual and auditory, primarily music, stimuli with only a handful of studies exploring the aesthetic potential of linguistic stimuli. In the present study, we investigate for the first time the effects of personality traits on phonaesthetic language ratings. Twenty-three under-researched, “rarer” (less learned and therefore less known as a foreign language or L2) and minority languages were evaluated by 145 participants in terms of eroticism, beauty, status, and orderliness, subjectively perceived based on language sound. Overall, Romance languages (Catalan, Portuguese, Romanian) were still among the top six erotic languages of the experiment together with “Romance-sounding,” but less known languages like Breton and Basque. Catalan and Portuguese were also placed among the top six most beautiful languages. The Germanic languages (Swedish, Norwegian, Danish, and Icelandic) were perceived as more prestigious / higher in terms of status, however to some degree conditioned by their recognition / familiarity. Thus, we partly replicated the results of our earlier studies on the Romance language preferences (the so-called Latin Lover effect) and the perceived higher status of the Germanic languages and scrutinized again the effects of familiarity / language recognition, thereby calling into question the above mentioned concepts of the Latin Lover effect and the status of Germanic languages. We also found significant effects of personality traits (neuroticism, extraversion, and conscientiousness) on phonaesthetic ratings. Different personality types appreciated different aspects of languages: e.g., whereas neurotics had strong opinions about languages’ eroticism, more conscientious participants gave significantly different ratings for status. Introverts were more generous in their ratings overall in comparison to extroverts. We did not find strong connections between personality types and specific languages or linguistic features (sonority, speech rate). Overall, personality traits were largely overridden by other individual differences: familiarity with languages (socio-cultural construals, the Romanization effect – perceiving a particular language as a Romance language) and participants’ native language / L1.